A new Cretaceous fossil mammal locality from the Bass Coast of southeastern Australia. Issue 3 (2nd October 2022) - Rich, Thomas H.; Lowery, Melissa; Hall, Michael; Kool, Lesley; Bevitt, Joseph; White, Matt; Vickers-Rich, Patricia
Abstract: Mesozoic mammals from the polar regions of Australian Gondwana are exceptionally rare. The recovery of a partial jaw attributable to the australosphenid Ausktribosphenos nyktos from a new locality along the Bass Coast of Victoria is, therefore, significant because it comes from an uppermost Barremian to lowermost Aptian grit with abundant plant material that differs lithologically from other previously productive laminated sandstone deposits. We interpret this as evidence for a floodplain habitat that was distant from local water bodies. The identification of a new Cretaceous mammal locality in Australia highlights the exciting prospects for future fossil discoveries. Thomas H. Rich [trich@museum.vic.gov.au ] Museums Victoria, Melbourne, Victoria, 3001, PO Box 666, Australia Melissa L. Lowery [melissalouiselowery@gmail.com ] 82 Williams Street, Inverloch, Victoria, 3996, Australia Michael Hall [mike.hall@monash.edu ] School of Earth, Atmosphere and Environment, Monash University, Victoria, 3800, Australia Lesley Kool [koollesley@gmail.com ] Museums Victoria, Melbourne, Victoria, 3001, Australia PO Box 666; School of Earth, Atmosphere and Environment, Monash University, Victoria, 3800, Australia Joseph Bevitt [joseph.bevitt@ansto.gov.au ] Australian Centre for Neutron Scattering, Australian Nuclear Science and Technology Organisation, Lucas Heights, Nsw, 2234, Australia Matt White [fossilised@hotmail.com ] University of New England, Armidale, Nsw, 2350, Australia Patricia Vickers-Rich [pat.rich@monash.edu, prich@swin.edu.au ] School of Earth, Atmosphere and Environment, Monash University, Victoria, 3800, Australia; Department of Chemistry and Biotechnology, Swinburne University of Science and Technology, Hawthorn, Victoria, 3122, Australia .